Analysis of growth of coffee arabic in relation to water soil transpirable fraction - Pizetta, Samuel Cola; Rodrigues, Rogério Rangel; Ribeiro, Wilian Rodrigues; dos Reis, Edvaldo Fialho; Colodetti, Tafarel Victor (Coffee Science - ISSN 1984-3909, 2016)
Understanding the need of the coffee water is essential for proper crop management, aiming obtaining higher yields and rational use of water resources. In this sense, the objective was to analyze the influence of fraction of transpirable soil water on the growth of Arabica coffee and evaluate the recovery of plants after drought. The experiment was carried out in Agricultural Sciences Center of the Federal University of Espírito Santo, located in Alegre-ES municipality, consisting of two treatments and four replicates. The treatments corresponded to the absence (T0) and presence of soil water deficit (Td), applied at 30 and 90 days after planting. The T0 kept the moisture close to field capacity soil. In Td, the deficit was applied until the plants reach 10% relative sweating T0. The variables analyzed were transpiration, leaf area and plant height. To evaluate the recovery of coffee after water stress, the plants were kept for 30 days with moisture content around field capacity. According to the results, a reduction in the variables in higher values of breathable fraction of water in soil treatment applied 30 days after planting, compared to 90 days. The plants has shown better recovery trend after the water deficit in the treatment applied at 90 days after planting.